LESUNG BANARATA Karawitan di Akar Rumput - Sigit Astono (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2002)
For the Banarata community, Iesung(a hollowed wood for pounding rice) is not only used for pounding rice, but also for expressing aesthetic feeling that has to do with religion and solidarity among the members of the community. The music of the lesung is also important for stimulating the feeling of pride for the owners. That is why even when this music was not played for almost three decades — for political and belief reasons — it can attract the spirit (seniangat), love, proud, musicality. In addition, it can also be used for expressing other feelings.